1966
DOI: 10.1136/ard.25.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Retroperitoneal Fibrosis Associated with an Arteritis

Abstract: The first report in the world literature of the condition which is now generally known as idiopathic retroperitoneal fibrosis was that of Albarran (1905), but the first report in the English language did not appear until that of Ormond (1948). Since then many further case reports have been published, but the aetiology of the condition remains obscure.The disease usually presents as a urological problem when the mass of retroperitoneal fibrous tissue causes deviation or obstruction of one or both ureters often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The original aortic damage might be due to methysergide or other vasoactive agents in some cases, and to aortitis similar to that seen in connective tissue diseases in the majority. Some of the cases in the series have already been reported (Jones and Alexander, 1966;Turner-Warwick, Nabarro, and Doniach, 1966;Jose, 1967); to these authors, and to other surgeons, physicians, and pathologists too numerous to name, my thanks are due for permission to study their patients. I am grateful to the Department of Medical Photography, Addenbrooke's Hospital, for Figures 1 and 4-7.…”
Section: Discussionmentioning
confidence: 98%
“…The original aortic damage might be due to methysergide or other vasoactive agents in some cases, and to aortitis similar to that seen in connective tissue diseases in the majority. Some of the cases in the series have already been reported (Jones and Alexander, 1966;Turner-Warwick, Nabarro, and Doniach, 1966;Jose, 1967); to these authors, and to other surgeons, physicians, and pathologists too numerous to name, my thanks are due for permission to study their patients. I am grateful to the Department of Medical Photography, Addenbrooke's Hospital, for Figures 1 and 4-7.…”
Section: Discussionmentioning
confidence: 98%
“…The concept of a systemic inflammatory nature of CP is also borne out by the histologic similarities of CP with large-vessel vasculitis, such as the prominent adventitial inflammation and the involvement of vasa vasorum (24). Moreover, autopsy studies have shown that moderate adventitial inflammation and fibrosis may not be limited to the abdominal aorta, but also involve its thoracic portion (25,26). In fact, aortic arch syndrome has been reported in CP, confirming the possible involvement of the thoracic aorta (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, 3 of the 4 subjects with RPF had coronary artery diseases that are rare complications of Takayasu arteritis ( I I), and 2 of them died of cardiac ischemia (8,9). Because of differences in the distribution of the aortitis, typical features of Takayasu arteritis, such as pulselessness and dizziness, may be lacking in patients with RPF associated with aortitis.…”
Section: Retroperitoneal Fibrosis Associated With Aortitismentioning
confidence: 99%